2021
DOI: 10.37478/jpm.v2i2.925
|View full text |Cite
|
Sign up to set email alerts
|

The Utilization of Artificial Intelligence Components in Technology Era’s Learning

Abstract: This study was to analyze the importance of component utilization of Artificial Intelligence (AI) in learning. This study was acknowledged by the results of a survey to the secondary school education teachers in the Subject Teachers' Association (MGMP) for Citizenship Education field in Cimahi as many as 42 schools and 146 teachers through the Google Form application and 104 teachers responded according to the Krejcie and Morgan tables. The method used in this research was descriptive survey. Based on the surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…One of the most conspicuous obstacles is that 80.36% of the teachers are digital immigrant generations so that these teachers include teachers who have limited human resources, namely lack of technology (internet) skills. Halimah et al (2021) found that most teachers in the learning process do not always use technological aids, social networks or use current issues, sometimes even never even assign learning materials broadly and deeply. Certainly, in online learning, many are affected by both teachers and students.…”
Section: Figure 3 Rpp Used By Teachers In Online Learningmentioning
confidence: 99%
“…One of the most conspicuous obstacles is that 80.36% of the teachers are digital immigrant generations so that these teachers include teachers who have limited human resources, namely lack of technology (internet) skills. Halimah et al (2021) found that most teachers in the learning process do not always use technological aids, social networks or use current issues, sometimes even never even assign learning materials broadly and deeply. Certainly, in online learning, many are affected by both teachers and students.…”
Section: Figure 3 Rpp Used By Teachers In Online Learningmentioning
confidence: 99%